(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The importance of the work is in the investigation of quercetin and lipoate effect in treatment of experimental diabetes. Objective. To investigate quercetin and lipoate effect on the enzymes of the antioxidant system (superoxide dismutase and catalase) in experimental diabetes Material and methods. The investigation was made on 55 white rats. The animals were divided into four groups: the 1st — a control one (14 rats), the 2nd — a group under study (14 rats) — animals with diabetes without using drugs; the 3rd — a group under study (12 rats) — animals with diabetes and using of lipoic acid; the 4th — a group under study (15 rats) — animals with diabetes and using of quercetin. Activity of superoxidedismutase and catalase was determined in homogenates of the retina and blood serum. Results. The application of lipoic acid and quercetin had a marked effect on the rate of enzymatic elimination of highly reactive forms of oxygen in the retina and organism in diabetes mellitus. Conclusion. 1. The application of the drugs of lipoic acid and quercetin considerably activates the anzymes of the antioxidant system in the retina of white rats under the conditions of stpreptosotocyn diabetes. Activity of catalase in the application of lipoate increased by 53.8 and 52.5 % in 2 and 6 months correspondingly; and in using quercetin — by 50.8 and 46.2 % in comparison with animals without using the drug. Activity of superoxide dismutase in application of lipoic acid was increased by 33.6 % (in 2 months) and 34.5 % (in 6 months), and quercetin effect increased activity of superoxide dismutase by 27.9 % and 29.8 % accordingly. 2. On the whole the application of the lipoic acid has more expressive effect on the enzymatic system of extinction of free-radical forms of oxygen in the eye retina in development of experimental diabetes.